2016
DOI: 10.1186/s13756-016-0114-7
|View full text |Cite
|
Sign up to set email alerts
|

Infections caused by extended-spectrum beta-lactamases producing Enterobacteriaceae: clinical and economic impact in patients hospitalized in 2 teaching hospitals in Dakar, Senegal

Abstract: BackgroundInfections caused by extended-spectrum beta-lactamases producing Enterobacteriaceae (ESBL-E) are of major concern in clinical practice because of limited therapeutic options effective to treat them. Published studies showed that ESBL-E, widely spread in Europe, United States or Asia; are also frequent in Africa. However, the impact of ESBL-E infections is yet to be adequately determined in Sub-Saharan African countries, particularly in Senegal.The aim of our study was to estimate the incidence rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…14 From our observations, the mortality ratio in Obstetrics versus Gynecology cases is 1: 11.2 or in other words, Gynecological patients with SSI and ESBL (+) have a 11.2x chance of dying than in Obstetrics. This is in accordance with the results of a study from Senegal which states that SSI cases with ESBL (+) and comorbid malignancies have a higher Case Fatality Rate (16).…”
Section: Resultssupporting
confidence: 92%
“…14 From our observations, the mortality ratio in Obstetrics versus Gynecology cases is 1: 11.2 or in other words, Gynecological patients with SSI and ESBL (+) have a 11.2x chance of dying than in Obstetrics. This is in accordance with the results of a study from Senegal which states that SSI cases with ESBL (+) and comorbid malignancies have a higher Case Fatality Rate (16).…”
Section: Resultssupporting
confidence: 92%
“…151 However, multidrug-resistant ESBLproducing organisms observed in several studies are usually acquired from contaminated hospital environments, 152 with increased risk of mortality, especially among preterm babies. 153 In Mali, typing of ESBL Enterobacteriaceae among bacteraemic children and adults from two referral hospitals showed a high rate of cross transmission between patients and the spread of strains from one hospital to another due to patient transfers. 154 This finding underlines the crucial need for…”
Section: Discussionmentioning
confidence: 99%
“…Hijazi et al (2016) also reported a similar finding in Lebanon with male children having a higher colonization frequency (33.9%) of ESBL-E in contrast to their female counterparts that had a frequency of (15.9%). However this observation is a deviation from the normal trend of having more bacterial isolates from female urine samples since they were more at risk of acquiring urinary tract infection compared to their male counterparts (Ameri et al, 2014 (Ndir et al, 2016). Antibiotic resistance is a global problem which varies across countries as a result of hygiene levels in hospital and antibiotic management policies.…”
Section: Discussionmentioning
confidence: 99%